Randomized clinical trial of topical tranexamic acid after reduction mammoplasty. Issue 11 (October 2015) - Ausen, K.; Fossmark, R.; Spigset, O.; Pleym, H.
<x xml:space="preserve">Abstract</x> Background The antifibrinolytic drug tranexamic acid is currently being rediscovered for both trauma and major surgery. Intravenous administration reduces the need for blood transfusion and blood loss by about one‐third, but routine administration in surgery is not yet advocated owing to concerns regarding thromboembolic events. The aim of this study was to investigate whether topical application of tranexamic acid to a wound surface reduces postoperative bleeding. Methods This was a randomized double‐blind placebo‐controlled trial on 30 consecutive women undergoing bilateral reduction mammoplasty. On one side the wound surfaces were moistened with 25 mg/ml tranexamic acid before closure, and placebo (saline) was used on the other side. Drain fluid production was measured for 24 h after surgery, and pain was measured after 3 and 24 h. Postoperative complications including infection, seroma, rebleeding and suture reactions were recorded. Results Topical application of tranexamic acid to the wound surface after reduction mammoplasty reduced drain fluid production by 39 per cent (median 12·5 (range 0–44) versus 20·5 (0–100) ml; P = 0·038). Adverse effects were not observed. There were no significant differences in postoperative pain scores or complications. Conclusion Topical application of dilute tranexamic acid reduced bleeding in this model. The study adds to the evidence that this simple procedure may reduce wound bleeding after surgery. Registration number: NCT01964781 ( http://www.clinicaltrials.gov).